Budidaya Udang Vannamei (Litopenaeus vannamei) Semiintensif dengan Metode Sirkulasi Tertutup Untuk Menghindari Serangan Virus [The Semiintensive Culture Of Litopenaeus vannamei By Closed Circulation Method To Prevent Virus Attack] - Slamet Subyakto; Dede Sutende; Moh. Afand; Sofiati Sofiati (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract The failure of vannamei shrimp culture often caused by virus attack, i.e. WSSV, TSV and IMNV. So that it need an alternative method like closed circulation method and probiotic application. Closed circulation is culture method without water circulation where as an additional water will do to change loss water, caused by evaporation and culture waste water. This kinds of probiotic ar Bacillus subtilis, Nitrosomonas, Nitrobacter, Saccaromyces, Rhodobacter and Rhodococcus. The aim of these research are preventing virus attack through closed circulation method and probiotic 2 2application. These culture used two culture ponds (3000 m , density 60 species/m ) and two reservoir ponds 2(2000 m ) for 105 days. The first culture pond (A) produced 2895 kg of vannamei shrimp (size 60, SR 96.5 % and FCR 1.3). The second culture pond (B) produced 3025 kg of vannamei shrimp (size 58, SR 97.4 % and FCR 1.28).